A Video and Case-Based Transport Curriculum for Neonatal-Perinatal Medicine Trainees Using a Flipped Classroom Methodology - Carly M. Gisondo; Gary Weiner; Kate Stanley (Association of American Medical Colleges, 2021)
Introduction Neonatal-perinatal medicine (NPM) providers actively manage medical transports. However, there is wide variation in transport education among fellowship programs. Using the flipped classroom methodology, we developed a video and case-based transport education curriculum. Methods A national needs assessment identified safety, communication skills, and physiology as the most important aspects of transport management. Three 10-minute video modules and two 20-minute case-based discussions were developed to address this content. Using the flipped classroom format, seven NPM fellows from all three postgraduate years of training took part in the curriculum by individually viewing each video followed by participation in group case-based discussions. Cognitive and affective outcomes were assessed using a knowledge and attitude pretest, individual video module posttests, and a postcurriculum follow-up survey. Results NPM fellows showed significant improvements in transport knowledge and reported increased confidence in their ability to perform important transport roles. Case discussions were adaptable to learners who had different levels of training and had variable transport experience. Case discussions were successfully executed both in person and by video telecommunications during the 2020 COVID-19 pandemic. Discussion This transport curriculum addressed a national education gap in NPM fellowship training. Using the flipped classroom methodology, cognitive and affective objectives were achieved by improving knowledge and confidence in transport skills among NPM learners. The video and case-based formats were easily implemented, applicable to multiple types of learners, and adaptable to different environments.